Financial Institutions Management - Millon Cornett Marcia; Saunders Anthony (Mcgraw Hill International Editions, 2011)
Introduction, Why are Financial Institutions Special?, Financial Services: Depository Institutions, Financial Services: Insurance, Financial Services: Securities Brokerage and Investment Banking, Financial Services: Mutual Funds and Hedge Funds, Financial Services: Finance Companies, Risk of Financial Institutions, Measuring Risk, Interest Rate Risk, Market Risk, Credit Risk: Individual Loan Risk, Credit Risk: Loan Portfolio and Concentration Risk, Off - Balance - Sheet Risk, Foreign Exchange Risk, Sovereign Risk, Technology and Other Operational Risks, Liquidity Risk, Managing Risk, Liability and Liquidity Management, Deposit Insurance and Other Liability Gurantees, Capital Adequacy, Product and Geographic Expansion, Futures and Forwards, Options and Caps and Floors and Collars, Swaps, Loan Sales, Securitization, Index.